Planejamento da expansão da transmissão: solução do modelo DC usando algoritmo genético e o fluxo de carga linearizado implementados na linguagem Python - Souza, Bruno Henrique Santiago de (2022)
The study of Transmission Expansion Planning (TEP) is of great importance to meet the continuous growth in electricity demand. The objective of TEP using the DC model is to obtain the optimal longterm plan for the expansion of the transmission system in order to indicate where new transmission lines should be allocated. The objective of this work is to develop a computational tool in the Python programming language to solve the DC model TEP problem, using the genetic algorithm together with the linearized load flow optimization model, applied in the6busGarversystem. The proposed methodology is carried out by applying the GA and the linearized load flow optimization model using specific Python libraries. One hundred iterations were performed, with one hundred generations and forty individuals, and with that, the final value of two hundred thousand dollars was obtained for the construction of seven new transmission lines. The results obtained showed that it is possible to use the proposed methodology to solve the problem of the PET model DC.